Literatura e imagem em catálogo de perdas: paradigmas formadores de leitura - Bueno, Ademir de Godoy (2024)
The interarts combination is a contemporary trend in the various artistic manifestations, especially from modernism, in which the arts break boundaries between writing and image and establish dialogues in their productions. In this PhD thesis, we intend to propose a historical review that not only seeks to observe the way in which interartistic correspondences were carried out, but also discusses the relevance of this correspondence commonly used throughout the comparison between the arts and, more precisely, the comparisons between literature and photography. The reflection centered on the construction of images – both in the narrative and in the painting – assumes singular importance for interartistic research insofar as it functions as a point of convergence, as well as divergence, between the two arts. The discussions about the construction of images also lead us to another problem inherent to interarts studies, which is the reading of literary and pictorial images. In the historical review, we will discuss the historical modifications of Horace's expression Ut pictura poesis which designated the comparative studies between literature and painting for centuries. The main objective of this doctoral research is to establish and analyze the correspondence between literature and photography in Catálogo de perda (2017) by João Anzanello Carrascoza and Juliana Monteiro Carrascoza. To do so, we established a relationship between aesthetic experiments that are maintained, especially in the avant-garde movements which boosted interartistic dialogues and created new possibilities of representation in an approximation between the arts. The confluence between literature and photography in the selected work goes beyond the thematic level and shows how photographic syntax is incorporated into the literary language of João Carrascoza. Memory becomes a common axis to literary and photographic language, as well as revealing the author's desire for an introspective dive. The literary and artistic dialogue enhances the word-image interaction and the attentive and skillful look of reading. The double imagetic narration (verbal and visual) generates a new meaningful place for literary reading. The literary work allows deep reflection on artistic making of man and his existence by establishing this approximation of languages